Perinatal outcomes of intrauterine transfusion for the surviving twin in monochorionic twin gestation involving a single fetal demise. Issue 8 (2nd June 2020) - Kanda, Masako; Noguchi, Shohei; Yamamoto, Ryo; Kawaguchi, Haruna; Hayashi, Shusaku; Murakoshi, Takeshi; Ishii, Keisuke
Abstract: Aim: This study aimed to evaluate the feasibility and outcome of intrauterine transfusion (IUT) for the surviving co‐twin in monochorionic diamniotic (MCDA) twin gestations involving single intrauterine fetal death (sIUFD). Methods: Cases of MCDA twin gestations involving emergent IUT for co‐twins experiencing acute feto‐fetal hemorrhage (AFFH) subsequent to sIUFD during the second trimester were reviewed. Fetal anemia was confirmed via fetal blood sampling, and perinatal data were retrieved from medical charts to determine the outcomes of surviving co‐twins. A poor outcome at 28 days of age was defined as fetal death, neonatal death or neurological impairment such as severe intraventricular hemorrhage or cystic periventricular leukomalacia (PVL). Results: This study included 16 cases of sIUFD diagnosed at a median of 22.5 weeks of gestation (range: 18–25 weeks). The median interval in hours between diagnosis of fetal demise and IUT was approximately 4.2 (0–22) hours. All cases achieved IUT without significant intraoperative complications. Four cases experienced a fetal loss of the co‐twin, whereas 12 co‐twins were born alive (including 9 preterm births), with only 1 poor outcome in a preterm infant with PVL. Conclusion: IUT may be a feasible prenatal intervention for surviving co‐twins with AFFH. However, more extensive or pooled studies are needed to determine the efficacy of this intervention.